Correlation of Nuclear Morphometry with Clinicopathologic Parameters in Malignant Breast Aspirates - Kalhan, Shivani; Garg, Shilpa; Satarkar, Rahul; Sharma, Puja; Hasija, Sonia; Sharma, Sonia (South Asian Journal of Cancer, 2021)
Objectives The primary objective of this study was to correlate nuclear morphometric parameters with clinicopathologic features such as cytologic grade, tumor size, lymph node status, mitotic index, and histopathologic grade. Secondary objective was to quantify nuclear changes on malignant breast aspirates using morphometry.Material and Methods Forty-five cases of carcinoma breast diagnosed on cytology were included in this study. These were graded into cytologic grades 1, 2, and 3 as per Robinson’s cytologic grading system.Nuclear morphometry was done in all cases on smears stained with Papanicolaou stain.Clinicopathologic parameters including cytological grade, tumor size, lymph node status, mitotic count, and histological grade were correlated with nuclear morphometric parameters, namely, area, perimeter, shape, long axis, short axis, intensity, long-run emphasis, total run length, and T1 homogeneity.Results There were 9 cases in cytologic grade 1, 26 in grade 2, and 10 cases in cytologic grade 3. Histopathology showed 42 cases of infiltrating duct carcinoma, not otherwise specified (IDC, NOS) and 3 cases (6.7%) of ductal carcinoma in situ (DCIS). IDC (NOS) included 6, 27, and 9 cases in grades 1, 2, and 3, respectively. Majority of our cases had a tumor size less than 5 cm (n = 38, 84.4%) and had positive nodes (n = 30, 66.7%). Correlation of cytologic and histopathologic grades (including DCIS) with all morphometric features except long-run emphasis was statistically significant. Correlation of morphometry with tumor size yielded significant results for nuclear area, perimeter, long and short axes, and intensity with p < 0.05. Study of lymph node status (positive/negative) versus morphometry showed a highly significant statistical association with all the geometric as well as textural parameters. Mitotic count was significantly associated with all the geometric parameters and one textural parameter (total run length).Statistics Continuous variables were presented as mean ± standard deviation and compared using the two-tailed, independent sample t-test and one-way analysis of variance test. Tests were performed at significance level of 0.05.Conclusion Morphometry is an objective technique which holds immense promise in prognostication in breast carcinoma.
Keywords: breast; carcinoma; morphometry; cytology